2010
DOI: 10.1159/000288774
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Psychological Distress of Persons Involved in the Care of Patients with Alzheimer Disease Predicts Falls and Fractures in Their Care Recipients

Abstract: Background/Aims: Elderly patients with dementia have a higher risk of falls and fractures as compared to cognitively intact elderly subjects. To investigate whether psychological distress of the caregiver might predispose older persons with Alzheimer disease (AD) to falls and fractures, we performed a prospective cohort study. Methods: A consecutive series of 110 subjects with dementia underwent baseline and follow-up clinical and functional evaluations. The burden of the caregivers was recorded at baseline. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…3 In our study, the favorable rs8099917 TT genotype was found in 100% of the rs12979860 CC patients compared to 31% of CT and 10% of TT patients only. Among the 42 rs12979860 CT patients, off-therapy responses were significantly higher in the 13 rs8099917 TT than in the 29 rs8099917 TG patients, with a rate of sustained virological response of 23% versus 3%, P ¼ 0.045 and of HBsAg loss of 23% versus 0%, P ¼ 0.007.…”
Section: Replysupporting
confidence: 47%
See 3 more Smart Citations
“…3 In our study, the favorable rs8099917 TT genotype was found in 100% of the rs12979860 CC patients compared to 31% of CT and 10% of TT patients only. Among the 42 rs12979860 CT patients, off-therapy responses were significantly higher in the 13 rs8099917 TT than in the 29 rs8099917 TG patients, with a rate of sustained virological response of 23% versus 3%, P ¼ 0.045 and of HBsAg loss of 23% versus 0%, P ¼ 0.007.…”
Section: Replysupporting
confidence: 47%
“…[2][3][4] In this respect, we reported that Hp-I is frequently detected in neurodegenerative diseases including CD and Alzheimer's disease (AD) and Hp eradication may positively influence AD manifestations at 2-and 5-year clinical endpoints, 2 thereby supporting a role for this common infection in the pathobiology of the disease. Others also found that AD patients infected by Hp tended to be more cognitively impaired, and patients with dementia have a higher risk of falls and fractures 3 ; Hp-I may also be responsible for osteoporosis.…”
Section: Replymentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] In this respect, we reported that Hp-I is frequently detected in neurodegenerative diseases including CD and Alzheimer's disease (AD) and Hp eradication may positively influence AD manifestations at 2-and 5-year clinical endpoints, 2 thereby supporting a role for this common infection in the pathobiology of the disease. Others also found that AD patients infected by Hp tended to be more cognitively impaired, and patients with dementia have a higher risk of falls and fractures 3 ; Hp-I may also be responsible for osteoporosis.…”
Section: Helicobacter Pylori Induced Cognitive Dysfunction Might Be Amentioning
confidence: 99%